Contraction Reserve With Ineffective Esophageal Motility on Esophageal High-Resolution Manometry is Associated With Lower Acid Exposure Times Compared With Absent Contraction Reserve. (19th December 2020) - Quader, Farhan; Rogers, Benjamin; Sievers, Tyson; Mumtaz, Shaham; Lee, Mindy; Lu, Thomas; Gyawali, C. Prakash
Abstract : INTRODUCTION: Ineffective esophageal motility (IEM) is a minor motor disorder with potential reflux implications. Contraction reserve, manifested as augmentation of esophageal body contraction after multiple rapid swallows (MRS), may affect esophageal acid exposure time (AET) in IEM. METHODS: Esophageal high-resolution manometry (HRM) and ambulatory reflux monitoring studies were reviewed over 2 years to identify patients with normal HRM, IEM (≥50% ineffective swallows), and absent contractility (100% failed swallows). Single swallows and MRS were analyzed using HRM software tools (distal contractile integral, DCI) to determine contraction reserve (mean MRS DCI to mean single swallow DCI ratio >1). Univariate analysis and multivariable regression analyses were performed to determine motor predictors of abnormal AET in the context of contraction reserve. RESULTS: Of 191 eligible patients, 57.1% had normal HRM, 37.2% had IEM, and 5.8% had absent contractility. Contraction reserve had no affect on AET in normal HRM. Nonsevere IEM (5–7 ineffective swallows) demonstrated significantly lower proportions with abnormal AET in the presence of contraction reserve (30.4%) compared with severe IEM (8–10 ineffective swallows) (75.0%, P = 0.03). Abnormal AET proportions in nonsevere IEM with contraction reserve (32.7%) resembled normal HRM (33.0%, P = 0.96), whereas that in severe IEM with (46.2%) or without contraction reserve (50.0%) resembled absent contractility (54.5%, P ≥ 0.6). Multivariable analysis demonstrated contraction reserve to be an independent predictor of lower upright AET in nonsevere (odds ratio 0.44, 95% confidence interval 0.23–0.88) but not severe IEM. DISCUSSION: Contraction reserve affects esophageal reflux burden in nonsevere IEM. Segregating IEM into severe and nonsevere cohorts has clinical value.